Impact of Industry Digitalization on Recruitment of Employment Opportunities - Idayanti, Soesi; Siswanto, Siswanto (Jurnal Dinamika Hukum, 2022)
Industrial digitization will change the character of future jobs. The digital era makes all things easier to carry out. All things that easier to carry out include something that relate to production process, service process, and others process. However, the digital era also has a negative or disruptive effect on the economy, especially in terms of employment, both opportunities and labor needs.This study aims to find out the current labor regulations related to industrial digitization, and to find out what impacts of industrial digitization on employment opportunities. The results of this study indicate that regulations regarding employment related to industrial digitization have been regulated in Law Number 13 of 2003 concerning Manpower and the Law on Job Creation.The digitization of industry and the way new digital technologies are reconfiguring the way goods and services are produced. Likewise with various job opportunities, because industrial digitalization has also changed many types of jobs.Keywords:Industrial Digitization, Industrial Revolution, Manpower.